1998
DOI: 10.1073/pnas.95.17.9819
|View full text |Cite
|
Sign up to set email alerts
|

A 1.3-Å resolution crystal structure of the HIV-1 trans-activation response region RNA stem reveals a metal ion-dependent bulge conformation

Abstract: The crystal structure of an HIV-1 transactivation response region (TAR) RNA fragment containing the binding site for the trans-activation protein Tat has been determined to 1.3-Å resolution. In this crystal structure, the characteristic UCU bulge of TAR adopts a conformation that is stabilized by three divalent calcium ions and differs from those determined previously by solution NMR. One metal ion, crucial to the loop conformation, binds directly to three phosphates in the loop region. The structure emphasize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 48 publications
8
147
0
Order By: Relevance
“…Conversely, Zacharias and Hagerman (42) observed a decrease in bending for 3U-RNA with an increase in Mg 2+ concentration, whereas our data suggest that 3T-DNA is slightly more bent in the presence of Mg 2+ . This difference could result from specific metal binding to the RNA but not DNA bulge or from stacking or other differences between this DNA and RNA (43,44). The ability of X-ray interferometry to probe beyond structure averages should render this technique particularly valuable in determining the origin of such differences.…”
Section: X-ray Interferometry To Probe the Effects Of Bulge Sequence Andmentioning
confidence: 99%
“…Conversely, Zacharias and Hagerman (42) observed a decrease in bending for 3U-RNA with an increase in Mg 2+ concentration, whereas our data suggest that 3T-DNA is slightly more bent in the presence of Mg 2+ . This difference could result from specific metal binding to the RNA but not DNA bulge or from stacking or other differences between this DNA and RNA (43,44). The ability of X-ray interferometry to probe beyond structure averages should render this technique particularly valuable in determining the origin of such differences.…”
Section: X-ray Interferometry To Probe the Effects Of Bulge Sequence Andmentioning
confidence: 99%
“…Mitochondrial membrane potentials were measured at 25 8C using a membrane potential-sensitive dye 3, 39-dipropylthiadicarbocyanine iodide, diS-C 3 -(5) (Molecular Probes, Inc+) (Hauser et al+, 1996)+ An SLM-Aminco 8000 spectrofluorometer was set at 620 nm for excitation and 670 nm for emission to detect fluorescence of the dye+ Initially, fluorescence measurement of diS-C 3 -(5) was taken (Hauser et al+, 1996), added at a final concentration of 5 mM in buffer (20 mM HEPES-KOH, pH 7+4, 0+6 M sorbitol, 25 mM KCl, 10 mM MgCl 2 , 1 mM EDTA, 2 mM KH 2 PO 4 , 1 mg/mL fatty acid-free bovine serum albumin, 5 mM NADH, 5 mM succinate, and 1 mM ATP) at 25 8C+ Addition of mitochondria was used to initiate the measurement of membrane potential+ Presence of a membrane potential is detected by a decrease of fluorescence, measured in arbitrary units, depicted as a downward deflection in the graph+ Some of -7, 15-21 and 22-28: 40, 80, 120, 160, 200, 40 and 4 pmol [50, 100, 150, 200, 250, 50 and 5 ϫ 10 3 cpm], respectively; Lanes 8-14: 10, 50, 100, 150, 200, 100 and 5 pmol [30, 150, 300, 450, 600, 300 and 15 ϫ 10 3 cpm], respectively) were incubated with isolated mitochondria and the extent of nuclease protection assayed by gel electrophoresis+ Lanes 6, 13, 20 and 27 represent RNAs digested with nuclease in the absence of mitochondria which were used as controls for digestion+ Lanes 7,14,21 and 28 Figure 1 were chemically synthesized (Oligos Etc+)+ Other RNAs also used in the importation assays include the 107-nt spliced leader RNA (Sturm et al+, 1999), the 169-nt ND7+2x RNA, which is a portion of the NADH subunit 7 mRNA with a mutation in the anchor region (Byrne et al+, 1996), B. subtilis pre-tRNA Asp (Waugh et al+, 1989), and several synthetic RNAs (Xeragon Oligoribonucleotides): TAR RNA (Ippolito & Steitz, 1998), 59-AGAGCA CUUGGAGCUCU-39; GAC RNA, 59-GGGGGAAAAAAA CCCCC-39; NF RNA, 59-CUCUCCCUCCUUACCAC-39; 59 leader RNA, 59-GGGAGACCGGAAUUCGAGCUCGGUA CCCAAAAU-39; ⌬ND7 RNA (Blanc et al+, 1999), 59-GAGCAGUGUUUACCGAUGA-39; 6C RNA, 59-GCUAUG UCUGCUAACUUGCCCCCC-39; 6U RNA, 59-GCUAUGU CUGCUAACUUGUUUUUU-39+ RNA folding was performed using MFOLD 3+0 on the M+ Zuker website at http:// mfold2+wustl+edu/;mfold/rna/form1+cgi+ The free energies of the most stable RNA folds in kilocalories per mole are as follows: 59 leader, Ϫ9+4; TAR, Ϫ5+1; GAC, Ϫ8+4; 6C, Ϫ0+3; 6U, Ϫ0+7; ⌬ND7, Ϫ1+5; NF, no folding+ Plasmids were linearized by restriction digestion and used as templates in T7 in vitro run-off transcription reactions containing T7 RNA polymerase, ribonucleotides and the appropriate buffer (Milligan et al+, 1987;Cunningham & Ofengand, 1990)+ Uniformly labeled RNAs were transcribed in vitro in the presence of [a-32 P]UTP (NEN) in the reaction+ The 59-end labeled RNAs were incubated with [g-32 P]ATP (NEN) and T4 polynucleotide kinase for 1 h at 37 8C in T4 polynucleotide kinase buffer (GIBCO-BRL)+ The synthetic RNAs were 39-end labele...…”
Section: Measurement Of Membrane Potentialmentioning
confidence: 99%
“…The helix II region of 5S rRNA, with a single-nucleotide bulge at a conserved position, has been suggested to interact with a number of proteins+ Structural alterations introduced in helix II were shown to interfere with the TFIIIA binding if the changes disrupted the Watson-Crick base paring (Theunissen et al+, 1992;McBryant et al+, 1995)+ Helix II is also found to interact with the ribosomal proteins L18 and L25 (Shpanchenko et al+, 1996) and its stability influences the association with L18 (Meier et al+, 1986)+ Although the Watson-Crick base pairing is crucial for helix II function, its sequence varies considerably between organisms (Fig+ 1)+ The role of the bulge residue in helix II is not clear in these interactions+ However, the fact that it is at a conserved position speaks for its importance+ The presence of this bulge is highly conserved throughout evolution, and its identity varies with major phylogenetic families+ This residue is likely involved in specific 5S rRNA-protein recognition or interaction in prokaryotic and eukaryotic ribosomes (Woese & Gutell, 1989;Zhang et al+, 1989)+ Bulged residues have been shown to participate in numerous biological functions, including protein-RNA recognition (Wu & Uhlenbeck, 1987;Dingwall et al+, 1990), the self-splicing of group II intron and nuclear pre-mRNA (Sharp, 1987), and folding of large RNA molecules (Woese & Gutell, 1989)+ A single cytosine bulge in the iron responsive element (IRE) RNA is found particularly important in binding of proteins that regulate the iron homeostasis (Jaffrey et al+, 1993)+ These bulged nucleotides might engage in direct contact with proteins and other RNA structural motifs, or play structural roles in recognition by introducing distortion of the RNA helix, thus providing a characteristic shape for binding+ High-resolution structural information on singlenucleotide bulges in duplex structures is available for DNA (Joshua-Tor et al+, 1992), RNA (Ennifar et al+, 1999;Ippolito & Steitz, 2000), chimeric duplex (Portmann et al+, 1996), DNA•RNA hybrid (Sudarsanakumar et al+, 2000), as well as an RNA-protein complex (Valegard et al+, 1997)+ Structures of RNA duplexes containing multiplenucleotide bulges are also determined (Ippolito & Steitz, 1998;Wedekind & Mckey, 1999)+ Interestingly, conformational flexibility seems to be a predominant feature for single-base bulges+ Multiple conformations for the bulged residue are found in many crystal structures of oligonucleotide duplexes containing single-nucleotide bulges (Po...…”
Section: Introductionmentioning
confidence: 99%